Determinants of Carbon Emission Disclosure: An Empirical Study on Indonesian Manufacturing Companies - Lutfiana Pratiwi; Bunga Maharani; Yosefa Sayekti (The Indonesian Accounting Review, 2021)
Due to the worsening environmental issues e.g, climate change, the stakeholders impose greater demand and pressure more towards the companies of caring about the environment. The emergence of carbon accounting is a supplement to the adoption of Kyoto Protocol. However, the government has not applied carbon accounting to all companies in Indonesia, because of non-explicit laws and low quality of human resources. Various studies have been conducted to find the determinant factors for companies to make carbon emission disclosure. This research aims at examining the influence of type of industry, profitability, company size, environmental performance, and audit firm reputation on the carbon emission disclosure of manufacturing companies listed on the Indonesia Stock Exchange years 2016-2019. It employed a purposive sampling technique and obtained 290 observations and the data were analyzed using Ordinary Least Square. The shows that type of industry, profitability and company size influence carbon emission disclosure. However, this research does not successfully show the influence of environmental performance and reputation of public accountant office on carbon emission disclosure.